Lowering the Level of Egg Yolk in Diluent or Removal of Seminal Plasma with Standard Egg Yolk Level do not Help in the Efficient Freezing of Buck Semen - Bhat, Ghulam Rasool; Lone, Farooz Ahmad; Khatun, Arjuma; Anand, Mukul; Dhariya, Rahul; Rana, Sanchi; Shah, Riaz Ahmad; Ahmad, Haidar Ali; Hussain, Ishraq (The Indian Journal of Animal Reproduction, 2025)
The aim of this investigation was to compare the sperm quality in removal or intact seminal plasma buck semen frozen in tris diluent containing 20% and 2.5% egg yolk and to test whether lowering egg yolk level of diluent or removal of seminal plasma with standard egg yolk level helps in efficient freezing of buck semen. A total of 18 fresh ejaculates were divided into three aliquots of 500µl each corresponding to three treatment groups designated as BT1 (tris with 20% egg yolk, washed), BT2 (tris with 20% egg yolk, non-washed) and BT3 (tris with 2.5% egg yolk, non-washed). Semen aliquots of BT1 (washed), BT2 (unwashed) and BT3 (unwashed) were diluted and frozen with standard procedures. Post thaw semen quality was carried out with phase contrast microscopy, fluorescent microscopy, Computer Assisted Sperm Analysis (CASA) and flow cytometry. Majority of fertility associated with post-thaw sperm quality parameters evaluated by CASA, Flow Cytometry and subjective methods were significantly (p